PENGEMBANGAN MODUL PENDIDIKAN KONSERVASI MANGROVE BERBASIS ECOLOGICAL CITIZENSHIP UNTUK MASYARAKAT PESISIR DI SERANG - BANTEN - Novi Utami Rosyid (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2019)
The Serang - Banten coastal community was affected by various environmental, social and economicproblems due to abrasion. The main factor causing abrasion was the degradation of mangroveecosystems in the Serang Coastal region which results from various activities of the Serang coastalcommunity that are not environmentally friendly. Environmental education is the best solution tosolve environmental problems. One method that can be practiced in the environmental education ofthe Coastal Serang community is the ecological citizenship method. This method requires learningresources to facilitate its application in effectively educating the public through learning modules.The aim of this research is to develop an ecological citizenship-based mangrove conservationmodule for coastal communities in Serang - Banten. The research method was the 3D modeldevelopment method (define, design, develop) which was a modification of the 4D model bySugiyono, et.al (2015). The results of the study are in the form of an ecological citizenship mangroveconservation module that can be used by ministries, institutions and the community as a source ofenvironmental education learning for mangrove conservation in the coastal area of Serang - Banten.